2016
DOI: 10.1038/nmat4772
|View full text |Cite
|
Sign up to set email alerts
|

Single-platelet nanomechanics measured by high-throughput cytometry

Abstract: Haemostasis occurs at sites of vascular injury, where flowing blood forms a clot, a dynamic and heterogeneous fibrin-based biomaterial. Paramount in the clot’s capability to stem haemorrhage are its changing mechanical properties, the major driver of which are the contractile forces exerted by platelets against the fibrin scaffold 1. However, how platelets transduce microenvironmental cues to mediate contraction and alter clot mechanics is unknown. This is clinically relevant, as overly softened and stiffened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
153
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(163 citation statements)
references
References 37 publications
10
153
0
Order By: Relevance
“…Myosin II is the main force source for platelet contraction and Rho kinases are required for the regulation of platelet contraction (Calaminus et al 2007; Myers et al 2017; Ono et al 2008). Under the treatment of blebbistatin and Y-27632, platelets adhered and spread with normal morphology, and low-level integrin tensions in platelets mapped by 12 pN ITS displayed the regular ring-shaped force distribution with the similar force intensity as the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myosin II is the main force source for platelet contraction and Rho kinases are required for the regulation of platelet contraction (Calaminus et al 2007; Myers et al 2017; Ono et al 2008). Under the treatment of blebbistatin and Y-27632, platelets adhered and spread with normal morphology, and low-level integrin tensions in platelets mapped by 12 pN ITS displayed the regular ring-shaped force distribution with the similar force intensity as the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, multiple techniques including cell traction force microscopy (Henriques et al 2012), atomic force microscopy (Lam et al 2011; Lee and Marchant 2001), elastomers (Myers et al 2017; Qiu et al 2014) and micro-post assays (Feghhi et al 2016; Liang et al 2010) have been applied to the bulk force measurement in individual platelets. These pioneering methods have enabled the measurement of bulk platelet forces and advanced the study of platelet mechanobiology to a single cell level.…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional TFM suffers from low measurement throughput and artifacts related to variations in hydrogel mechanical properties. To address these drawbacks, a chip‐based high‐throughput platelet contraction cytometer was developed recently . The chip‐based contraction cytometer uses microfabrication technology to fabricate a large array of fibrinogen passivated microdot pairs on a hydrogel substrate with varied stiffness to assess the nanomechanics of hundreds of individual platelets under physiologically relevant conditions.…”
Section: Traction Force Measurementsmentioning
confidence: 99%
“…The readout of contractile force output is based on measurement of lateral displacement of 2 adjacent fibrinogen microdots by a single activated platelet. Using a platelet contraction cytometer, Myers et al revealed that platelet‐generated contractile force during clot formation requires both biochemical (eg, thrombin) and mechanical (eg, substrate stiffness) inputs and the mechanosensitive contraction is highly dependent on the Rho/ROCK pathway. Furthermore, assessment of platelet contractile forces from patients with Wiskott‐Aldrich syndrome and MYH9 disorder (nonmuscle myosin IIa mutations) on a platelet contraction cytometer showed that up to 30% of these platelets from patients with cytoskeleton‐related platelet disorders exhibit the near‐zero contractile forces on stiffer substrates, while this was limited to only 6% in healthy controls.…”
Section: Traction Force Measurementsmentioning
confidence: 99%
“…Based on the same measurement principles as TEG, ROTEM, and Sonoclot, microengineered devices assessing viscoelasticity alteration during blood clotting using magnatoelastic transducer 4 , quartz crystal microbalance 5 , acoustic resonator 6 , ultrasound radiation 7 , laser speckle rheology 8 , cantilever beam oscillation 9 , dielectric sensor 10 , etc., have been reported. Using microtechnology, a few microscale devices have been specifically developed for platelet contractile force measurements down to the single cell level based on micropost array 11 , atomic force microscopy 12 , micropatterned fibrinogen array 13 , traction force microscopy 14 , etc. These devices are believed to be capable of monitoring the contractile function of platelets and thus identifying the cause of bleeding and guiding pro- and anti-coagulant therapies.…”
mentioning
confidence: 99%